Karakterisasi Morfologi dan Anatomi Tanaman Manggis dan Kerabatnya (Garcinia spp.) di Taman Buah Mekarsari - NIDYASARI, RR. SYAFIRA; AKMAL, HILDA; ARIYANTI, NUNIK SRI (Jurnal Sumberdaya Hayati, 2018)
Mangosteen (Garcinia mangostana) cultivation has problems in terms of fruit quality and rooting system. This problem is solved by Mekarsari Fruit Garden by developing the technology of double rootstock seedling that is by combining two mangosteen seedling into one plant through the pasting process. Characterization of the collection of mangosteen plants and its species of relatives (Garcinia spp.) is needed to seek superior characters used for the technology of double rootstock seedlings, cultivar development, and management and preservation of mangosteen germplasm. This study aims to record and compare morphological and anatomical characters of mangosteen and its relatives collected in Taman Buah Mekarsari. The study was carried out by collecting the sample and characterizing the morphological structure using mangosteen descriptor, observing the leaf paradermal anatomy, and collecting secondary data. Observation on the morphological characteristics of mangostana (G. mangostana) and its relatives (G. celebica, G. dulcis, G. forbesii, and G. malaccensis) showed variations on the fruit characters, such as the shape is spherical, ovate or spherical flattened apex and base; the rind color is bright yellow, deep red, and bright red; the flavor is sour, sour sweet, or sweet. The anatomical character of the mangosteen leaf and four species of its relatives show the paracytic stomata on the abaxial surface only except on the leaf of G. forbersii, which is found on the abaxial and adaxial sustance, the epidermal cells are square to rectangular, the wall is straight or slighty winding except that of G. forbesii which is sharply winding or zig-zag